2016
DOI: 10.18632/oncotarget.12956
|View full text |Cite
|
Sign up to set email alerts
|

FDA-approved medications that impair human spermatogenesis

Abstract: We herein provide an overview of the single-ingredient U.S. Food and Drug Administration (FDA)-approved drugs that affect human spermatogenesis, potentially resulting in a negative impact on male fertility. To provide this information, we performed an in-depth search of DailyMed, the official website for FDA-approved drug labels. Not surprisingly, hormone-based agents were found to be the drugs most likely to affect human spermatogenesis. The next category of drugs most likely to have effects on spermatogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 80 publications
2
20
0
1
Order By: Relevance
“…The current reproductive toxicity testing should be able to provide useful results for clinical extrapolation. However, as noted above, our current study and previous studies about spermatotoxicity [3,105,106] have shown that studies in animals have relatively low predictive value for human toxicity. In some cases, the lack of useful findings is due to the high doses of the compounds used in the toxicity studies.…”
Section: Difficulties Associated With Animal Testing For Spermatotoxisupporting
confidence: 42%
See 3 more Smart Citations
“…The current reproductive toxicity testing should be able to provide useful results for clinical extrapolation. However, as noted above, our current study and previous studies about spermatotoxicity [3,105,106] have shown that studies in animals have relatively low predictive value for human toxicity. In some cases, the lack of useful findings is due to the high doses of the compounds used in the toxicity studies.…”
Section: Difficulties Associated With Animal Testing For Spermatotoxisupporting
confidence: 42%
“…The most important findings of the present study include the following: only 27% (63/235) of the drugs that had a negative effect in animals reported in the drug label were found to have a documented negative impact on human sperm (in the drug labels or literature). Further, a previous study [3] showed that fewer than half of the drugs with labels indicating that they adversely affected human sperm had similar findings in animals. In addition, for more than half of the drugs found to negatively affect animal spermatogenesis or spermatozoa, Based on studies of combination treatment the impact in humans is unclear either because no testing or surveillance has been performed, or because the results have not been reported.…”
Section: Difficulties Associated With Animal Testing For Spermatotoximentioning
confidence: 73%
See 2 more Smart Citations
“…It has been shown that exposure to CD causes decrease in epididymal sperm in rats without any changes in morphology of reproductive organs 60 . It was suggested that any drug that affect spermatogonia could lead to defects in sperm maturation and spermatogenesis 61 . We did not perform fertility tests, as studies have shown that even a 50–60% decline in sperm count will have no appreciable effect on fertility in mice (Schurmann et al ., 2002; Zhang et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%